LightBOX - Sithravel, Ratnakala; Mustafa Kamal, Rafeah; Ibrahim, Rahinah; Lye, Munn Sann; Perimal, Enoch Kumar; Dahlan, Nur Dalilah; Ibrahim, Normala (Universiti Putra Malaysia Press, 2017)
Dynamic overhead white LED ambient lighting is more conducive to an individual’s morning psycho-physiological wellbeing when compared to the constant lighting in workplaces where there is minimal natural daylight penetration or a windowless work space.